STRUCTURAL LINGUISTICS IN THE PSYCHOANALYTICAL CLINIC - Jonas Ribeiro, Magno (Revista Gênero e Interdisciplinaridade, 2023)
The present work aims to demonstrate the importance of structural linguistics, at the base of the clinical structure of Jacques Lacan’s psychoanalysis. considering that psychoanalysis is a knowledge developed by Sigmund Freud, considered the father of psychoanalysis, it was Lacan who emphasized the structural basis of how we could understand the psychoanalytic theoretical discourse, introducing sciences from other fields of knowledge, in this case, structural linguistics , as a guiding theory to understand such knowledge. finally, the present work has, in its importance, to point out the theoretical need that Lacan had, in making use of structural linguistics to deepen his reflections about the clinical discourse, and its importance in the understanding of the attendances.